Nutrition for recovery in aquatic sports - Burke, L. M.; Mujika, I. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Postexercise recovery is an important topic among aquatic athletes and involves interest in the quality, quantity, and timing of intake of food and fluids after workouts or competitive events to optimize processes such as refueling, rehydration, repair, and adaptation. Recovery processes that help to minimize the risk of illness and injury are also important but are less well documented. Recovery between workouts or competitive events may have two separate goals: (a) restoration of body losses and changes caused by the first session to restore performance for the next and (b) maximization of the adaptive responses to the stress provided by the session to gradually make the body become better at the features of exercise that are important for performance. In some cases, effective recovery occurs only when nutrients are supplied, and an early supply of nutrients may also be valuable in situations in which the period immediately after exercise provides an enhanced stimulus for recovery. This review summarizes contemporary knowledge of nutritional strategies to promote glycogen resynthesis, restoration of fluid balance, and protein synthesis after different types of exercise stimuli. It notes that some scenarios benefit from a proactive approach to recovery eating, whereas others may not need such attention. In fact, in some situations it may actually be beneficial to withhold nutritional support immediately after exercise. Each athlete should use a cost-benefit analysis of the approaches to recovery after different types of workouts or competitive events and then periodize different recovery strategies into their training or competition programs.